2019
DOI: 10.4103/ijt.ijt_7_19
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology of hair follicle epithelium in patients of recurrent and recalcitrant dermatophytosis: A diagnostic cross-sectional study

Abstract: Context: Recurrent and recalcitrant dermatophytosis is a major evolving health problem in India. Histopathology is important in the diagnosis of recurrent and resistant cases, as it is postulated that hair follicle epithelium is affected, acting as the reservoir leading to recurrence and recalcitrance. Aims: This study aims to study histopathology of hair follicle epithelium in patients of recurrent and recalcitrant dermatophytosis. Settings and Design: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 18 publications
(24 reference statements)
0
9
0
Order By: Relevance
“…3 Detection of fungal hyphae is not always possible with haematoxylin and eosin staining, and as in the reported case, periodic acid-Schiff or Grocott methenamine silver are often used to aid in visualisation. 7 Dermatophytosis has been described in a small number of bears in the literature. 8,9 M. gypseum was diagnosed in a pet bear (species unknown) and successfully treated with topical iodine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Detection of fungal hyphae is not always possible with haematoxylin and eosin staining, and as in the reported case, periodic acid-Schiff or Grocott methenamine silver are often used to aid in visualisation. 7 Dermatophytosis has been described in a small number of bears in the literature. 8,9 M. gypseum was diagnosed in a pet bear (species unknown) and successfully treated with topical iodine.…”
Section: Discussionmentioning
confidence: 99%
“…Dermatophytes have been visualised in deep infections in cases of feline mycetoma, 4 feline 5 and canine 6 pseudomycetoma and dermatophytic furunculsis 3 . Detection of fungal hyphae is not always possible with haematoxylin and eosin staining, and as in the reported case, periodic acid–Schiff or Grocott methenamine silver are often used to aid in visualisation 7 …”
Section: Discussionmentioning
confidence: 99%
“…[ 10 ] A few recent studies have postulated that presence of fungal hyphae in hair follicle could serve as a reservoir and enable clinical resistance, recurrence, and chronicity resulting in chronic and recurrent dermatophytosis. [ 6 7 ]…”
Section: Discussionmentioning
confidence: 99%
“…Study of histopathology is becoming increasingly important in the assessment of recurrent dermatophytosis in view of the findings of a few recent studies that have shown the presence of fungal elements within the hair follicle unit or epithelium. [ 6 7 ] These fungal elements act as a reservoir, leading to recurrence and recalcitrance of dermatophytosis. Dermatophytic infection of vellus hair in sites other than the scalp, may also give rise to recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…Histologic identification of fungal elements remains difficult. 1 Special stains like Grocott-methenamine silver and periodic acid–Schiff increase the detection 2 but the gold standard remains culture and morphologic identification of the fungi itself. 1 In situ hybridization (ISH) is a method being used for fungal identification and as such, refinements on the technique have been developing.…”
Section: Introductionmentioning
confidence: 99%